2003
DOI: 10.1080/10255840310001606080
|View full text |Cite
|
Sign up to set email alerts
|

A Human Model for Road Safety: From Geometrical Acquisition to Model Validation with Radioss

Abstract: In order to investigate injury mechanisms, and to provide directions for road safety system improvements, the HUMOS project has lead to the development of a 3D finite element model of the human body in driving position. The model geometry was obtained from a 50th percentile adult male. It includes the description of all compact and trabecular bones, ligaments, tendons, skin, muscles and internal organs. Material properties were based on literature data and specific experiments performed for the project. The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…Understanding the effects induced by postural changes on soft organs and skeleton of the trunk are of major importance for various applications like radiotherapy (Kim et al, 2007;Koelbl et al, 1999), ergonomics (Harrison et al, 2000), surgery simulation and crash study (Behr et al, 2003). Furthermore, quantifying the postural effects could facilitate the adaptation of numerical models to various applications: currently numerical models are often built from medical imaging in a standard position.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effects induced by postural changes on soft organs and skeleton of the trunk are of major importance for various applications like radiotherapy (Kim et al, 2007;Koelbl et al, 1999), ergonomics (Harrison et al, 2000), surgery simulation and crash study (Behr et al, 2003). Furthermore, quantifying the postural effects could facilitate the adaptation of numerical models to various applications: currently numerical models are often built from medical imaging in a standard position.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of modeling in the study of traumatology [4] has been shown for the majority of solid organs [2] and bony structures [30] with good clinico-pathologic correlation [22]. These models improve understanding of mechanical lesions [10] and the connections between the injured structures, irrespective of the chosen model [11,26].…”
Section: Conditions Producing the Mechanical Lesionsmentioning
confidence: 99%
“…Analysis of healthy splenic anthropomorphometric variability will provide information on the "typical shape" and orientation of this organ to develop numerical models while taking individual specificity into account. Thus, its integration into a comprehensive abdominal model will help to improve a virtual human model presently used in trauma study of all morphotypes (Behr et al, 2003). Indeed, trauma studies using accurate FE models are needed to develop new road safety systems based on the analysis of car crash accidents as well as clinical applications such as: surgical planning, decision making-support, and the development of new surgical tools and training software tools.…”
Section: Introductionmentioning
confidence: 99%